2023
DOI: 10.1002/anbr.202200106
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms by Which Liposomes Improve Inhaled Drug Delivery for Alveolar Diseases

Abstract: Diseases of the pulmonary alveolus, such as pulmonary fibrosis, are leading causes of morbidity and mortality, but exceedingly few drugs are developed for them. A major reason for this gap is that after inhalation, drugs are quickly whisked away from alveoli due to their high perfusion. To solve this problem, the mechanisms by which nano‐scale drug carriers dramatically improve lung pharmacokinetics using an inhalable liposome formulation containing nintedanib, an antifibrotic for pulmonary fibrosis, are studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…To ensure we can detect artifactual uptake of nanoparticles during the single-cell preparation process, we used as our positive control intratracheal instillation of liposomes (as opposed to our IV injection of anti-PECAM nanoparticles). We recently showed that after intratracheal instillation of liposomes into the lungs, the liposomes remain in the airspace of the lungs, not taken up cells, for many hours 68 ; ~80% of liposome remain extracellular, in the alveolar airspace, at 4 hours after liposome instillation. As hypothesized, after intratracheal instillation, liposomes had a very high nanoparticle cross-over index (NCI) of 51.2% ( Supp Fig 5 ), showing that the apparent marginated neutrophil uptake mostly occurred ex vivo , rather than in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…To ensure we can detect artifactual uptake of nanoparticles during the single-cell preparation process, we used as our positive control intratracheal instillation of liposomes (as opposed to our IV injection of anti-PECAM nanoparticles). We recently showed that after intratracheal instillation of liposomes into the lungs, the liposomes remain in the airspace of the lungs, not taken up cells, for many hours 68 ; ~80% of liposome remain extracellular, in the alveolar airspace, at 4 hours after liposome instillation. As hypothesized, after intratracheal instillation, liposomes had a very high nanoparticle cross-over index (NCI) of 51.2% ( Supp Fig 5 ), showing that the apparent marginated neutrophil uptake mostly occurred ex vivo , rather than in vivo.…”
Section: Resultsmentioning
confidence: 99%
“… NCT Active Ingredient Advanced Drug Delivery System Population Indication Key findings NA Nintedanib Liposomes Naïve mice Pulmonary Fibrosis An 8000 fold increase in AUC was identified when using liposomal delivery in comparison to oral free Nintedanib administration. The liposomal formulation demonstrated an enhanced efficacy of the drug with reduced side effects during in-vivo studies [ 58 ]. NC-6004 Cisplatin Micelle Patients over 18 years of age with histologically or cytologically confirmed stage IV squamous NSCLC Stage IV Non-small cell lung cancer Higher Cisplatin doses were better tolerated in patients within the study as no clinically significant indicators of neurotoxicity, nephrotoxicity or ototoxicity were observed [ 59 ].…”
Section: Investigational Clinical Studies and Patentsmentioning
confidence: 99%
“…17,18 In addition, large colloidal and polymeric systems exhibit limited penetration through mucus and pulmonary membrane permeability. [19][20][21][22] The objective of this work was therefore to design a novel drug delivery system that exhibits good mucus penetration, biocompatibility and tailorable cell and membrane permeability through key membrane barriers in the lungs.…”
Section: Introductionmentioning
confidence: 99%